Association between spot urinary sodium-to-potassium ratio and blood pressure among Chinese adults aged 18–69 years: the SMASH study - Xu, Chunxiao; Dong, Jing; Liu, Danru; Xu, Jianwei; Zhang, Bingyin; Lu, Zilong; Wang, Linhong; Tang, Junli; Zhang, Xiaochang; Ren, Jie; Yu, Xiaohui; Guo, Rui; et al. (Frontiers in Nutrition, 2024)
Excessive sodium and low potassium intake are involved in the development of hypertension.Growing evidence showed that sodium-to-potassium ratio (Na/K) was significantly associated with blood pressure (BP). However, studies on the dose-response relationship of spot urinary Na/K ratio with hypertension and BP in the general population are scarce, especially in a Chinese population. To address this gap, we utilized data from the post-intervention survey of the Shandong Ministry of Health Action on Salt and Hypertension (SMASH) project. Associations of Na/K molar ratio with hypertension prevalence and BP indices were analyzed using multivariable logistic and linear regression respectively, followed by subgroup analysis and interaction analysis. Restricted cubic spline model was used to explore the dose-response relationship. Informed by existing literature, we adjusted for potential confounding factors, including temperature and renal function, to assess the association and dose-response relationship. Overall, there were a non-linear positive association between Na/K and hypertension (OR:1.09, 95%CI: 1.08-1.11), and linear positive association of Na/K with systolic BP, diastolic BP and mean arterial pressure (β 0.53, 95%CI: 0.45-0.60; β 0.36, 95%CI: 0.31-0.41 and β 0.42, 95%CI: 0.36-0.47 ) respectively. The association was stronger in those with hypertension, female, 50~59 age group and those who were obese. Environmental temperature had little impact on associations. Our findings provide further evidence that spot urinary Na/K ratio is a simple, useful and convenient indicator for monitoring salt reduction and potassium increase which could be used in clinical and public health practices.